Place-making with goats and microbes: The more-than-human geographies of local cheese in Jämtland, Sweden. (February 2017) - Eriksson, Camilla; Bull, Jacob
Abstract: Since the 1940s Swedish rural policy has shaped agriculture and food production into a rational, large scale and specialised industry, focused on food hygiene. However, in Jämtland pockets of resistance remained where small-scale farmers continued to produce local cheeses. As rural policy has shifted towards favouring the local and traditional within Geographic Indication frameworks, these cheeses are receiving more attention from policymakers as well as consumers. During the last 10–15 years local cheese making has been revitalised with the introduction of sophisticated techniques and new knowledges on how to work with microbes to create more distinct, local cheeses. Bacteria cultures and moulds are treasured and explicitly considered in ways that were previously tacit. As this paper shows the development of these new cheese-making processes owe a lot to imported knowledge and microbes from France. The paper goes on to discuss how these 'cultural imports' combine with local knowledge and microbes to enable different narratives of locality, 'authenticity', and 'traditional' within contemporary cheese-making. Highlights: GI labels have only been awarded to industrial, not artisan, cheeses in Sweden. Artisan cheese is produced and narrated as a resistance to industrial agriculture. French and local microbes and practices are mixed in the creation of 'local cheese'. Three paradigms of responding to microbial agency in cheese making are identified.